ANALISIS KOMPARATIF PENDAPATAN USAHATANI KUBIS DAN WORTEL DI DESA KERINJING KECAMATAN DEMPO UTARA KOTA PAGARALAM - Muhammad Syarif, Yetty Oktarina (JASEP, 2025)
This research was conducted in Kerinjing Village, North Dempo Subdistrict, Pagaralam City, where the determination of the area was done purposively. This area was chosen as the location of the study based on data obtained from the Department of Agriculture and Plantation of Pagaralam City, that farming of Cabbages and Carrots was two mainstay commodities among other vegetables in North Dempo, Pagaralam City. The research was carried out in February 2018 until February 2019. The method used in this study is the survey method. Data collection methods used in this study are observation, questionnaires and direct interviews as a data collection tool. Data processing methods carried out are using income formula and t-test analysis to see the comparison of income. The calculation shows that cabbage and carrot farming in Kerinjing Village, North Dempo District, Pagaralam City produces an average income of Cabbage Farming Rp. Rp. 32,176,269 per season, and the average income of Carrot Farming is Rp. 36,086,888 per season. This shows that cabbage farming income is lower than the income of carrot farming.